2019
DOI: 10.7554/elife.41223
|View full text |Cite
|
Sign up to set email alerts
|

Valence-encoding in the lateral habenula arises from the entopeduncular region

Abstract: Lateral habenula (LHb) neurons are activated by negative motivational stimuli and play key roles in the pathophysiology of depression. Prior reports suggested that rostral entopeduncular nucleus (rEPN) neurons drive these responses in the LHb and rostromedial tegmental nucleus (RMTg), but these influences remain untested. Using rabies viral tracers, we demonstrate disynaptic projections from the rEPN to RMTg, but not VTA, via the LHb in rats. Using in vivo electrophysiology, we find that rEPN or LHb subpopulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 37 publications
5
45
0
Order By: Relevance
“…These processes fine-tune future strategies in similar situations (5,41,(45)(46)(47)(48). LHb and mVTA conveys information related to negative predictions and learns to respond to cues that predict aversive stimuli (3,42,(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…These processes fine-tune future strategies in similar situations (5,41,(45)(46)(47)(48). LHb and mVTA conveys information related to negative predictions and learns to respond to cues that predict aversive stimuli (3,42,(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Ontology analysis in the LHb pointed to functions in fast neural transmission (Glutamate and GABA) and membrane conductance as well. As the LHb is innervated heavily from the entopeduncular nucleus (EPN) co-releasing Glutamate and GABA (Herkenham and Nauta, 1979;Hong and Hikosaka, 2008;Lazaridis et al, 2019;Shabel et al, 2014) and the lateral hypothalamic area (LHA; both GABAergic and Glutamatergic innervations) (Lazaridis et al, 2019;Li et al, 2019), we found enrichments in genes that are components of GABA receptors (e.g. Gabra1, Gabrb1) and Glutamate receptors (e.g.…”
Section: Distinct Transcriptional Domains Between the Mhb And The Lhbmentioning
confidence: 94%
“…As part of the epithalamus, the habenula is well conserved across vertebrate species (Agetsuma et al, 2010;Amo et al, 2010;Bianco Isaac H and Wilson Stephen W, 2009;Lee et al, 2010;Stephenson-Jones et al, 2012), and in mammals, can be subdivided into medial (MHb) and lateral (LHb) subdivisions demarcated both anatomically and by patterned gene expression (Aizawa et al, 2012;Marburg, 1944). LHb neurons are almost entirely composed of SLC17A6 (VGlut2) expressing glutamatergic neurons, which receive synaptic inputs from regions such as the ventral pallidum (Golden et al, 2016;Knowland et al, 2017), lateral hypothalamic area (Lazaridis et al, 2019a;Lecca et al, 2017;Stamatakis et al, 2016), endopeduncular nucleus/globus pallidus (Hong and Hikosaka, 2008;Li et al, 2019;Shabel et al, 2012;Wallace et al, 2017), the ventral tegmental area (VTA) (Root et al, 2014;Stamatakis et al, 2013), and other regions . Glutamatergic LHb output neurons project to the VTA where they directly and indirectly regulate the activity of dopaminergic neurons to alter appetitive and aversive behaviors (Hong et al, 2011;Jhou et al, 2009;Lammel et al, 2012;Stamatakis and Stuber, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, 28 although adult-like responses may appear only later in ontogeny, it is possible that 29 larvae are capable of sensing and responding to the alarm cue in a different 30 manner [22,35]. 31 As larval and adult differences in kinematics, and sensitivity of as much as a 32 million-fold have been documented in many species [21], we explored the use of a 33 chamber size-matched to the larva that mimics the adult behavioral setup we had used 34 in the past to quantify the behavior of a solitary animal [37]. We complemented our 35 behavioral studies with neural activity imaging of transgenic lines expressing GCaMP6f.…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of activity patterns was seen, including 171 activity during and after the stimulus (Supplementary Figure 6). Thus, in addition to 172 areas predicted by direct connectivity with the olfactory bulb, the alarm substance 173 influences a number of other areas within the forebrain, including a structure involved 174 in processing negatively valenced stimuli [31].…”
mentioning
confidence: 99%